Embung Bandung Bondowoso Tourism Sustainability Strategy in Sidobandung Village, Balen District, Bojonegoro Regency - Amilis Setyandhinavia; Hartati Kartikaningsih; Setyo Tri Wahyudi (Jurnal Penelitian Pendidikan IPA, 2025)
Embung Bandung Bondowoso Tourism offers water tourism which originates from the Pacal River, Bojonegoro Regency. The choice for developing Embung Bandung Bondowoso tourism is because it is to utilize the embung which has been owned since 2020. Even though Bandung Bondowoso tourism has been open since February 1st 2022 and is currently still in the development process. The development of tourist villages is also a form of accelerating integrated village development to encourage social, cultural and economic transformation of villages. This research uses quantitative research methods. In this research, this was done by filling out a Multidimensional Scaling questionnaire and then analyzing the quantitative data obtained to answer the problem formulation regarding the sustainability status of the research location. The resulting index value shows that the 5 dimensions (ecological, social, economic, institutional and technological) of Embung Bandung Bondowoso Tourism already have very good sustainability status. The sensitive attributes that most influence sustainability and need to be considered are green open spaces, condition and availability of clean water, landslides, erosion and damage to water resources, conflicts of interest between residents, level of education, development of local products, community service providers and ease of reaching the location.